2012
DOI: 10.1017/s1751731112001310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for haemoglobin levels in pigs and iron content in pork

Abstract: Genetic parameters were obtained for iron content inm. longissimus dorsi(2255 records) and haemoglobin levels recorded at 5 (4974 records) and 21 (2405 records) weeks of age in two sire lines from September 2009 until January 2011. The measure of iron in pork was the mean of two replicates. Genetic associations of haematological traits with meat quality traits (2255 records), as well as growth rate and backfat (close to 60 000 records), were estimated. Analyses were based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Nevertheless, RV CBF in swine (0.99 Ϯ 0.17 ml•min Ϫ1 •g Ϫ1 ) appears to be only slightly higher than the value obtained in healthy humans (0.90 Ϯ 0.35 ml•min Ϫ1 •g Ϫ1 ) (46). The lower hemoglobin levels in these swine were not due to surgery or repetitive blood sampling as the values are similar to values obtained in a large cohort (Ͼ4,000) swine of similar age (21). Furthermore, hemoglobin levels were similar between control and PH swine both at rest and during exercise.…”
Section: Rv O 2 Delivery In Relation To Rv Function and Exercise Capacitysupporting
confidence: 73%
“…Nevertheless, RV CBF in swine (0.99 Ϯ 0.17 ml•min Ϫ1 •g Ϫ1 ) appears to be only slightly higher than the value obtained in healthy humans (0.90 Ϯ 0.35 ml•min Ϫ1 •g Ϫ1 ) (46). The lower hemoglobin levels in these swine were not due to surgery or repetitive blood sampling as the values are similar to values obtained in a large cohort (Ͼ4,000) swine of similar age (21). Furthermore, hemoglobin levels were similar between control and PH swine both at rest and during exercise.…”
Section: Rv O 2 Delivery In Relation To Rv Function and Exercise Capacitysupporting
confidence: 73%
“…Various animal and human studies have shown that the rate of iron transfer through the placenta depends on numerous factors including maternal iron status and species. It has also been shown that HbC is partly regulated by genetics in human and also in pigs [11, 12]. This may partly explain why maternal HbC and offspring HbC correlate.…”
Section: Resultsmentioning
confidence: 99%
“…Faster digesta outflow rate reduces rumen biohydrogenation rate of fatty acids (FA) [ 16 , 17 ], which in turn increases the supply of polyunsaturated fatty acids (PUFA) to the host animal and its products such as milk [ 17 , 18 ]. Subsequently, factors influencing ingestive and thereby digestive processes, like animal health status, diet, and their interaction [ 19 , 20 , 21 , 22 , 23 , 24 ], can alter the chemical composition and consequently nutraceutical characteristics of the final product for human consumption [ 25 ]. For example, Mangwe et al [ 26 ] reported that cows grazing PL produced milk with a greater content of PUFAs as compared to cows grazing a ryegrass sward [ Lolium perenne L. (RG)].…”
Section: Introductionmentioning
confidence: 99%